2016
DOI: 10.1002/anie.201602451
|View full text |Cite
|
Sign up to set email alerts
|

Direct Solar Charging of an Organic–Inorganic, Stable, and Aqueous Alkaline Redox Flow Battery with a Hematite Photoanode

Abstract: The intermittent nature of the sunlight and its increasing contribution to electricity generation is fostering the energy storage research. Direct solar charging of an auspicious type of redox flow battery could make solar energy directly and efficiently dispatchable. The first solar aqueous alkaline redox flow battery using low cost and environmentally safe materials is demonstrated. The electrolytes consist of the redox couples ferrocyanide and anthraquinone‐2,7‐disulphonate in sodium hydroxide solution, yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 25 publications
1
72
0
2
Order By: Relevance
“…In particular, 10-10 exhibits the lowest potentials vs SHE, indicating the highest full cell working potentials. [234,235] Recently, Wedege and co-workers improved this system and first reported solar aqueous alkaline RFBs. Interestingly, they found that the reduction potential of 2,6-DHAQ decreased with an increase in pH and reached the lowest value until pH = 12.…”
Section: Working-potential-orientedmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 10-10 exhibits the lowest potentials vs SHE, indicating the highest full cell working potentials. [234,235] Recently, Wedege and co-workers improved this system and first reported solar aqueous alkaline RFBs. Interestingly, they found that the reduction potential of 2,6-DHAQ decreased with an increase in pH and reached the lowest value until pH = 12.…”
Section: Working-potential-orientedmentioning
confidence: 99%
“…[232] Later, Aziz's group further developed an alkaline quinone flow battery to replace the corrosive acidic solution (Figure 12a), [233] in which 2,6-dihydroxyanthraquinone (2,6-DHAQ,10-11) and ferrocyanide (FeCy) were selected as the negative and positive active species, respectively. [235] This work offers an appealing opportunity for building grid-scale batteries for utilizing solar energy. However, the positive terminal of ferrocyanide has a pH-independent redox potential.…”
Section: Working-potential-orientedmentioning
confidence: 99%
“…20,21 This concept was demonstrated by the Weizmann Institute group in the late 1970s where they incorporated an additional battery electrode to make a three-electrode photoelectrochemical solar cell, where the electrical output could be split between charging the battery redox system and output during daylight and discharging the battery in the dark. 22 The Texas Instruments system for HBr photoelectrolysis was another example where inexpensive silicon microspheres with p-n and n-p junctions were incorporated into panels to produce hydrogen and Br 2 in the solution which flowed over the panels.…”
Section: Alternative Photoelectrochemical Storage Systemsmentioning
confidence: 99%
“…The photoreduction/oxidation of AQ species have been also proposed for energy‐related applications. For example, anthraquinone‐2,7‐disulphonic acid has been proposed to form the anolyte of solar rechargeable redox batteries . On the other hand, the incorporation of dispersed or polymer‐bound anthraquinone derivatives in polymeric packaging formulations has been proposed to scavenge unwanted oxygen .…”
Section: Introductionmentioning
confidence: 99%